GLP-1 RECEPTOR AGONISTS AND COLORECTAL CANCER: BIOLOGICAL PLAUSIBILITY AND CURRENT EVIDENCE - Bartosz Nowak; Miszela Kałachurska; Martyna Rożek; Maria Nowakowska; Aleksandra Kowalewska-Kurek; Aleksandra Lisowska; Oliwia Jerzyńska; Maria Sierant; Mateusz Gural; Constancia Esther Guy (International Journal of Innovative Technologies in Social Science, 2026)
Background: Colorectal cancer (CRC) remains one of the leading causes of cancer-related morbidity and mortality worldwide. Besides tumor-intrinsic factors, CRC risk and progression are strongly influenced by metabolic dysfunction - including obesity, insulin resistance, and T2DM. These implications emphasize the need for therapeutic strategies that address both tumor biology and the metabolic context. Objectives: This review examines the emerging role of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in colorectal cancer biology, synthesizing mechanistic, preclinical, and human evidence to evaluate their potential relevance beyond well-known glycemic control. Methods: We integrate experimental studies, animal models, and epidemiologic and clinical data to evaluate the effects of GLP-1RAs on colorectal cancer–related pathways, tumor growth and progression, and resulting clinical outcomes, with special attention given to metabolic and signaling mechanisms. Key Findings: Preclinical evidence suggests that GLP-1RAs may modulate pathways involved in cancer cell proliferation, survival, metabolism, angiogenesis, and invasion, including PI3K/Akt/mTOR, ERK, and hypoxia-associated signaling. In vivo models showcase inhibitory effects on tumor growth and metastatic potential, heightened in metabolically dysregulated settings. Human observational studies report heterogeneous but generally neutral to protective associations between GLP-1RA exposure and CRC risk, while randomized trials have primarily addressed cardiometabolic outcomes rather than being tumor-focused. Conclusions: Collectively, current evidence supports a biologically plausible role for GLP-1 receptor signaling in colorectal cancer growth and progression. Definitive clinical data are lacking, but evidence regarding GLP-1RAs justifies further investigation into their potential relevance.